Evidence for cosmic airburst in the Western Alps archived in Late Glacial paleosols. (18th May 2017) - Mahaney, W.C.; Somelar, Peeter; West, Allen; Krinsley, David; Allen, Christopher C.R.; Pentlavalli, Prasanna; Young, Jonathan M.; Dohm, James M.; LeCompte, Malcolm; Kelleher, Brian; Jordan, Sean F.; Pulleyblank, Coren; et al.
Abstract: Previous evidence for fragments of a cosmic airburst in the Western Alps has been shown to reside in weathering rinds in surface clasts of Late Glacial (LG) (mid-LG-post Allerød) deposits and in Ah horizons of several associated paleosols. In contrast to outlying strata, Younger Dryas (YD) paleosol horizons contain minor reworked airburst evidence that includes melted quartz/pyroxene grains, carbon spherules, glass-like carbon, and with minor differences in microbial populations. New data from LG paleosol profiles show REEs elevated above crustal abundance in several profiles of mid-Late Glacial age, along with elevated Pt concentrations, similar to those found at the YD Boundary in the Greenland Ice Sheet. Pt/Pd ratios that are elevated above background suggest an exogenic influx of Pt from meteoritic ablation and/or airbursts. An increasing number of localities with sedimentary time lines coeval with an airburst (12.8 ka) indicate the event was intercontinental, producing widespread conflagrations archived in local sediment sequences. This is the first instance worldwide in which evidence of the black mat event has been found both in weathering rinds and in paleosols in the Alps, with such information being applicable to reconnaissance beyond Earth such as in the case of Mars.